Preparation and characterization of multi-walled carbon nanotubes impregnated with polyethyleneimine for carbon dioxide capture. (2nd March 2015) - Lee, Min-Sang; Lee, Seul-Yi; Park, Soo-Jin
Abstract In this work, multi-walled carbon nanotubes impregnated with polyethyleneimine (MWCNT/PEI) have been prepared by wet-impregnation method with various PEI loadings for CO2 capture. The surface features and morphology were observed by scanning electron microscopy (SEM) and the textural properties were analyzed by N2/77 K adsorption–desorption isotherms. The CO2 adsorption capacity was evaluated by thermogravimetric analysis (TGA) method at 15% CO2 partial pressure. The MWCNT/PEI exhibited higher CO2 adsorption capacity than pristine MWCNTs. This result suggested that amine groups were attached on carbon surfaces in the impregnation process, leaving CO2 affinity sites on MWCNT surfaces. MWCNT/PEI exhibited superior cycle stability for CO2 capture, indicating great potential for application in post-combustion technology.